The Long-Term Association between Physical Activity and Weight Regain, Metabolic Risk Factors, Quality of Life and Sleep after Bariatric Surgery - Santos, Cláudia; Carvalho, Manuel; Oliveira, Leandro; Palmeira, António; Rodrigues, Luís Monteiro; Gregório, João (International journal of environmental research and public health, 2022)
Bariatric surgery is currently regarded as a safe and effective long-term procedure for the treatment of obesity and related comorbidities. We analyzed the association between physical activity (PA), weight regain, metabolic risk factors and quality of life in patients submitted to bariatric surgery. This study also aimed to preliminarily assess how physical activity and weight regain may be associated with sleep quality and sedentary behavior. This was an observational study, with retrospective data collection and a cross-sectional survey. Retrospective clinical data were collected from a sample of 84 individuals who had undergone bariatric gastric bypass surgery at least five years prior to the study period in an Integrated Responsibility Center for Obesity and Metabolic Diseases Surgery. The survey, developed from validated questionnaires and applied in telephone interviews, focused on health data, associated comorbidities, quality of life, physical activity, sedentary behavior and sleep. Descriptive and comparative statistics were performed with a 95% confidence level. Bariatric surgery induced a significant weight loss in the first year after surgery. Our analysis also revealed that lower levels of PA were associated with weight regain. Quality of life as well as sleep quality were inversely related to weight regain, as well as sedentary behavior in general. Primary and secondary outcomes of bariatric surgery can be better achieved if the practice of PA could be maintained for consecutive years.